A Metabolic Roadblock in Inflammatory Macrophages - O'NEILL, LUKE (My University, 2016)
n this issue of Cell Reports, Van den Bossche et al. (2016) reveal that, once the M1 macrophage forms, the accompanying metabolic alterations in the mitochondria are irreversible, preventing differentiation into the more homeostatic M2 macrophage.
PUBLISHED